Penerapan Terhadap Model Penerimaan Teknologi (TAM) Dengan Penerimaan Aplikasi E-Commerce Dalam Kehidupan Bisnis Usaha Mikro Masyarakat - Norenta Sitohang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The application of technology in all aspects is very important, especially during the Covid-19 pandemic, the changing times are urgent for the ability of the public to recognize technology in order to help survival both in seeking knowledge, the latest information and earning a living to survive. The covid-19 pandemic has forced many people to get used to using technology as a means of communication, transactions carried out in people's business lives. This impact responds to the behavior of the community to be able to survive and generate profits by getting to know technology in which there is a development of business models and transactions that become more flexible, in this case the application of TAM (Technology Acceptance Model) for community acceptance of e-commerce applications. in the community small business business by looking at several tests carried out by taking the respondent data of several community micro business actors with the help of the SPSS statistics application